Use of Secant Shear Modulus for Rutting Potential Assessment of Indonesian Wearing Course Mixtures - Iman Haryanto; Osamu Takahashi (The Baltic Journal of Road and Bridge Engineering)
Since shear modulus (G) indicates a resistance to shear deformation, the property should be essentially considered to evaluate the rutting potential. This study discusses a criterion of G for Indonesian wearing course mixture (IWCM) design. Simple unconfined compression test was conducted to calculate secant shear modulus (Gs) of IWCM. Gs is a ratio of shear strength (ts) to shear strain (g).ts and g were obtained from unconfined compressive strength and the strain transformation law, respectively. Wheel tracking test was conducted to verify validity of Gs as a rutting potential index of IWCM. Gs could rank the laboratory rutting performance of the designed mixtures as well as dynamic stability (DS). A relationship between Gs and DS suggests that over 28 MPa in Gs is equivalent to more than 800 cycles/mm in DS, within the scope of materials sources used in the present study. Gs can be one of rutting potential indicators of IWCM.